Bronze Age tell communities in context, Part 1, Critique, Europe and the Mediterranean an exploration into culture, society and the study of European prehistory - Kienlin, Tobias L. (Archaeopress archaeology, 2015)
This study challenges current modelling of Bronze Age tell communities in the Carpathian Basin in terms of the evolution of functionally-differentiated, hierarchical or 'proto-urban' society under the influence of Mediterranean palatial centres